1984
DOI: 10.1021/j150666a040
|View full text |Cite
|
Sign up to set email alerts
|

Laser pulse studies on the photoresponse of oxygen-evolving iron ruthenium sulfide (FexRu1-xS2). Mechanistic aspects

Abstract: Semiconducting Fe^Ru^Sj (£0 =1.1 eV) is able to evolve oxygen from aqueous electrolytes during illumination. From time-resolved photopotential and photocurrent measurements at FexRu1_xS2/electrolyte junctions performed with light of different wavelengths, additional information on the electrode properties and reaction behavior has been derived. The most important results are the following: The photoelectrochemical behavior is determined by a high number of surface states. As a consequence the band edges are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…will relax back to equilibrium prior to interaction with another laser pulse. The resulting decay observed for photopotential (open-circuit cell conditions) or photocurrent (short-circuit cell conditions) transients produced during such measurements have been used to probe interfacial kinetic parameters at a number of photoelectrodes including n-CdS (21)(22)(23)(24)(25), n-CdSe (22,23,33), n-WSe~ (31,35), n-MoSes (35,40), n-SnO2 (26,28,29), n-ZnO (27,28,30), n-Fe=Rul-xS2 (32), n-PtS2 (34), n-TiO2 (20,38,40), n-GaAs (39), n-InP (26,27), p-InP (36,37), and p-GaAs (40). Both photocurrent and photopotential techniques have demonstrated that the recorded transient photoresponse can be sensitive to the presence or absence of photoelectrode surface modifications .…”
mentioning
confidence: 99%
“…will relax back to equilibrium prior to interaction with another laser pulse. The resulting decay observed for photopotential (open-circuit cell conditions) or photocurrent (short-circuit cell conditions) transients produced during such measurements have been used to probe interfacial kinetic parameters at a number of photoelectrodes including n-CdS (21)(22)(23)(24)(25), n-CdSe (22,23,33), n-WSe~ (31,35), n-MoSes (35,40), n-SnO2 (26,28,29), n-ZnO (27,28,30), n-Fe=Rul-xS2 (32), n-PtS2 (34), n-TiO2 (20,38,40), n-GaAs (39), n-InP (26,27), p-InP (36,37), and p-GaAs (40). Both photocurrent and photopotential techniques have demonstrated that the recorded transient photoresponse can be sensitive to the presence or absence of photoelectrode surface modifications .…”
mentioning
confidence: 99%
“…The use of transient techniques in investigating photoelectrochemical cells has been introduced recently, in order to evaluate kinetic parameters in the p hotoelectrode processes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The relaxation of an open-circuit photopotential was examined theoretically for the special case where there is no interfacial electron or hole transfer (13).…”
mentioning
confidence: 99%
“…Also, a dye-sensitized system, SnOJrhodamine B, has been studied (6). Photocurrent transients obtained under short-~ circuit condition have also been studied (6)(7)(8)(9)(10)(11)(12). From the measured dependence of the decay time on the value of load resistance and additional capacitances, it has been shown that the photocurrent decay was controlled by the RC time constant of the cell (7,9,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation